2020
DOI: 10.3390/polym12092038
|View full text |Cite
|
Sign up to set email alerts
|

Aluminum-Filled Amorphous-PET, a Composite Showing Simultaneous Increase in Modulus and Impact Resistance

Abstract: Metal-plastic composites have the potential to combine enhanced electrical and thermal conductivity with a lower density than a pure metal. The drawback has often been brittleness and low impact resistance caused by weak adhesion between the metal filler and the plastic. Based on our observation that aluminum foil sticks very strongly to poly(ethylene terephthalate) (PET) if it is used as a backing during compression moulding, this work set out to explore PET filled with a micro and a nano aluminum (Al) powder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 38 publications
2
22
0
Order By: Relevance
“…It is more challenging to combine good tensile strength and impact in a more rigid polymer when filled. Other works using aluminium (Al) powder in polypropylene [ 26 ] and polycarbonate [ 41 ] also reported a deterioration of tensile strength and impact resistance. Nicolais and Nicodemo reported that styrene acrylonitrile (SAN) plastic, when filled with Al and Fe powders, led to an increase in modulus but a major decrease in tensile strength and elongation-to-break [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…It is more challenging to combine good tensile strength and impact in a more rigid polymer when filled. Other works using aluminium (Al) powder in polypropylene [ 26 ] and polycarbonate [ 41 ] also reported a deterioration of tensile strength and impact resistance. Nicolais and Nicodemo reported that styrene acrylonitrile (SAN) plastic, when filled with Al and Fe powders, led to an increase in modulus but a major decrease in tensile strength and elongation-to-break [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, we have taken the approach to start with a metal–plastic pair which has intrinsically good adhesion, so that the mechanical properties are not impaired, knowing conductivity will follow above a certain loading. We reported that amorphous PET filled with 15 vol.% of nodular (irregular shaped) Al particles gave a raised tensile modulus of 2.1 GPa, a strength that was invariant at ~57 MPa, and an increase in the notched Izod impact resistance (from 22 J/m for amorphous PET to 51 MPa), despite the elongation-to-break dropping from 96% to 14% [ 41 ]. It is uncommon in materials to get a simultaneous increase in modulus, strength, and impact, especially when the elongation-to-break decreases.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…On the whole, such products with PET as the raw material require longer molding cycles and higher mold temperatures to be well prepared [ 5 , 6 ]. Accordingly, the improvement of the PET crystallization rate has always been a research hotspot in the application of PET to structural materials [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%